The Atlas Bottom Mapping Recorder for Gapless Surveying of Inshore Waterways - Wentzell, Hubertus (The International Hydrographic Review, 2015)
Depth values are normally recorded by echo sounders as a single sounding profile. This has the disadvantage that no information is available from the space between these sounding profiles. For obtaining an impression of the depth of the sea bed side scanning can be used; this method is, however, not accurate enough in shallow water, and moreover the results are not true to scale. The Bottom Mapping Recorder avoids these disadvantages by using a large number of transducers mounted on outriggers or, if the ship is running transverse profiles across a river, mounted along the length of the keel. This Bottom Mapping Recorder combines the advantages of the accurate and true-to-scale information of the echosounder with the area imaging and extended coverage given by side scan. Its applications include both inshore and offshore surveying up to depths of 60 m, especially in rivers, canals and harbours.